Localization of Gender Equality Norms in Local Governance: A Case Study of Parepare City, Indonesia - Hadidah Sallimi; Sidik Jatmika (Khazanah Sosial, 2025)
This study examines the localization of gender equality norms within the governance framework of Parepare City, Indonesia, as part of international cooperation under the Maju Perempuan Indonesia untuk Penanggulangan Kemiskinan (MAMPU) program initiated in 2015. It aims to explain how global gender equality principles are translated, negotiated, and institutionalized within local policy and administrative systems. Employing a descriptive qualitative approach, the research draws on an extensive literature review and secondary data analysis, including government documents, local regulations, and program reports. The findings reveal that the Parepare City Government has made substantial progress in embedding gender equality norms through three interrelated dimensions: (1) policy reform, marked by the issuance of key local regulations such as Regional Regulation No. 5 of 2015 on Gender Mainstreaming in Regional Development and Regional Regulation No. 12 of 2015 on the Protection of Women and Children; (2) institutional expansion, through the strengthening of gender-responsive agencies, participatory planning forums (Musrenbang Perempuan and Musrenbang Anak), and cross-sectoral coordination; and (3) social transformation, reflected in growing public participation and increased reporting of gender-based violence cases. The study concludes that Parepare’s success in institutionalizing gender equality stems from its ability to align global frameworks with national mandates and local priorities, strengthened by credible intermediaries and sustained political commitment. The originality of this research lies in its focus on Parepare as an empirical model of localized gender governance, demonstrating how transnational gender norms can be integrated into local institutions, sustained beyond donor cycles, and advanced through rights-based and participatory governance at the subnational level in Indonesia.